J.M. Coetzee's Hispanic worlds - Perez Barra, C (2022)
My dissertation seeks to bring into critical focus the connections between J.M. Coetzee’s work and Hispanophone literature and culture, 1970 to the present day, in order to demonstrate in broad terms how he has used his symbolic capital to open a Hispanic and southern perspective onto Anglophone world literature. In four chapters, I develop different but complementary readings relating to what I call four distinctive Hispanic worlds. Having first established the methodology and the scope of Coetzee’s Hispanic involvements in the Introduction, in Chapter 1 I examine the translation, publication and reception of Coetzee’s works in the Hispanosphere (1983-2022) with a view to showing the distinctiveness of the circulation of world literature in a non-Anglophone global context with significant southern elements. In Chapter 2, I analyse Coetzee’s praxis as a reviewer, critic and scholar of Hispanophone letters (1973-2017), and demonstrate that throughout this period he was influenced by Hispanic literature even as he promoted it in diverse contexts and through varied intellectual praxes. In Chapter 3, I delve into Coetzee’s engagement with Borges and discuss how he develops his personal idea of the south in dialogue with the Argentine author, and through his academic, publishing and outreach efforts in the Southern Cone more broadly (2015-19). In Chapter 4, I show how these different worlds come together in the narrative landscape of the Jesus novels and their crepuscular fictional reality (2013-19) which, I argue, establishes a southern literature of Cervantean origin and allows for a Hispanic reading of Coetzee.